PEMANFAATAN APLIKASI SISTEM PAKAR UNTUK DIAGNOSA PENYAKIT PARU-PARU - Irianto, Suhendro Yusuf; Winarsih, - (IIB Darmajaya, 2011)
Expert system to diagnose lung disease was designed as a tool to diagnose the type of lung disease in particular. The knowledge obtained from various sources such as research and exposure to experts in the field and conducted a book-related lung disease. Inference in an expert system which is made using the method of Forward Chaining. Expert system will display a selection of symptoms that can be selected by the user to get the final result. At the end of the expert system will display the type of lung disease, information about lung disease and herbal medicine for lung disease. Keywords: expert system, lung disease